New Canadian natural health product regulations: a qualitative study of how CAM practitioners perceive they will be impacted - Ballantyne Peri; Boon Heather; Moss Karen; Kachan Natasha (BMC, 2006)
Abstract Background New Canadian policy to regulate natural health products (NHPs), such as herbs and vitamins were implemented on January 1st, 2004. We explored complementary and alternative medicine (CAM) practitioners' perceptions of how the new regulations may affect their practices and relationships with patients/consumers. Methods This was an applied ethnographic study. Data were collected in fall 2004 via qualitative interviews with 37 Canadian leaders of four CAM groups that use natural products as a core part of their practises: naturopathic medicine, traditional Chinese medicine (TCM), homeopathic medicine and Western herbalism. All interviews were transcribed verbatim and coded independently by a minimum of two investigators using content analysis. Results Three key findings emerged from the data: 1) all CAM leaders were concerned with issues of their own access to NHPs; 2) all the CAM leaders, except for the homeopathic leaders, specifically indicated a desire to have a restricted schedule of NHPs; and 3) only naturopathic leaders were concerned the NHP regulations could potentially endanger patients if they self-medicate incorrectly. Conclusion Naturopaths, TCM practitioners, homeopaths, and Western herbalists were all concerned about how the new NHP regulations will affect their access to the products they need to practice effectively. Additional research will need to focus on what impacts actually occur as the regulations are implemented more fully.